Bottlenecks Identification and Resilience Improvement of Power Networks in Extreme Events - Tu, Haicheng; Zhang, Xi; Xia, Yongxiang; Gu, Fengqiang; Xu, Sheng (Frontiers in Physics, 2022)
Extreme events are always accompanied with extensive failures and sharp performance degradation in power network. This paper is aim at deriving an effective scheme to identify the transmission bottlenecks and improve the power network resilience under extreme events. A greedy search scheme is designed for quick and slow restoration stage to obtain the largest power supply (LPS), which is a significant engineering indicator to power network. In the quick restoration stage, we use interior point optimization to adjust the operating parameters of undamaged components, and maximize the LPS with limited resources. It is worth pointing out that the LPS can not be further improved even by increasing the capacities of most transmission links. This phenomenon is due to the existence of transmission bottlenecks, which operate at their capacity limits. Thus, in the slow restoration stage, we identify these transmission bottlenecks and further improve the LPS by expanding the capacities of these links. Case studies show that the proposed greedy search scheme not only can greatly improve the LPS available to the post-disaster network, but also can accurately identify transmission bottlenecks. This work can provide practical insights for building resilient infrastructures, although the power network is the object of study.